Analysis of the implementation of Restful (Representational State Transfer) web services for data integration between information systems - I Nyoman Alit Arsana; I Made Pustikayasa; Ni Wayan Purnawati (Institute of Computer Science (IOCS), 2023)
The Library Information System and the SAT-IKA Information System (Sistem Infomasi Pangkalan Data Terintegrasi IAHNTP), which have their respective databases or are not integrated with each other, cannot be used together and can cause duplication and data inconsistency.Application of Web service technology enables interaction between heterogeneous software and can support data integration between information systems. The approach used is REST (Representational State Transfer) Web Service technology with JSON (Java Script Object Notation) format. Slim Micro Framework is used to code web applications and APIs (application programming interfaces) quickly and easily. The result of this research is data integration in each information system using a REST Web service with JSON data format so that data consistency is maintained and data redundancy is avoided